IDENTIFIKASI KOMPONEN ISOFLAVONOID PADA BUAH BALANGKASUA (Lepisanthes alata (Blume) Leenh.) - Susi Susi (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2019)
Balangkasua (Lepisanthes alata (Blume) Leenh.) is one of the exotic fruit typical of South Kalimantan, there are two kinds are yellow and purple-peel. This exotic fruit is still relatively low levels of consumption, this is because the harvest period is very short, not yet commercially grown, the growth area is in rural areas that are generally difficult to reach by public. Though the content of the nutritional value and phytochemical compounds that can be utilized. This research was aimed to determine the nutrient content in the pulp and peel and identify isoflavonoid component in the methanol extract of peel, pulp and seeds of purple peel balangkasua. Research result showed that pulp balangkasua contain protein of 8.40%, crude fiber of 21.76%, total acid of 26.90 mg KOH / g as well as vitamin C of 41.50 mg / 100 g, whereas in peel has a protein content of 4.20%, crude fiber of 37.83%, total acid of 13.47% and vitamin C of 38 mg/100 g).  Balangkasua was detected contain isoflavonoid compound there were equol and daidzein in seed, pulp was contained genestein, equol and genistin, and in the peel extract was contained genestein.